Trends in the Indian Hospitality Industry - Berry, Priyaanka (2008)
The purpose of this dissertation has been to analyse the current and future scenario of the hospitality industry in India. With India shining, the hospitality sector is quickly growing and maturing with time. It is constantly reinventing itself to compete on an international level. This dissertation aims to fill in some gaps which are quite evident in the existing literature review on the hospitality industry in India. There is not much published on this prospering sector. With the Indian economy booming, India is increasingly becoming an extremely sought after tourist and business destination. This research project tries to analyse the role and trends of the hospitality sector in Indian tourism. It looks in detail at the new developments in this sector, the rising demand and prices. It also examines the emergence of new elements such as MICE tourism and segmentation in the Indian hospitality industry. While some of the findings are consistent with the literature review, the individual interviews reveal a more accurate and in-depth point of view.